2013
DOI: 10.5367/te.2013.0332
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Relationships between Tourist Satisfaction and Destination Loyalty in a Segmented and Digitalized Market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 44 publications
2
3
0
1
Order By: Relevance
“…Pousttchi & Dehnert (2018) also suggest that characteristics of digital services affect the purchase decisions of retail banking customers. Our results are also in line with the findings of Neuts et al (2013), who conduct a research in the travel industry and state that characteristics of electronic services positively influence the satisfaction and destination loyalty of tourists. This result is in line with the findings of Nguyen et al (2020) who find that a better quality of digital technology implementation results in a higher overall customer perceived value.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pousttchi & Dehnert (2018) also suggest that characteristics of digital services affect the purchase decisions of retail banking customers. Our results are also in line with the findings of Neuts et al (2013), who conduct a research in the travel industry and state that characteristics of electronic services positively influence the satisfaction and destination loyalty of tourists. This result is in line with the findings of Nguyen et al (2020) who find that a better quality of digital technology implementation results in a higher overall customer perceived value.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Managerial implications indicated here can also be applicable to some degree in other industries such as banking and travelling considering some similarities with previous empirical studies in those industries (Dalcher & Shine, 2003;Neuts et al, 2013). Some suggestions may not be practical in travel and banking, though.…”
Section: 1theoretical and Managerial Implicationsmentioning
confidence: 58%
“…Besides, intention to visit was defined as individual's attitude response tendency to objects (Fishbein and Ajzen, 1977). The relationship between satisfaction and travel intention based on tourism experience has also been explored by previous studies (Cheunkamon et al, 2020; Neuts et al, 2013). For example, Cheunkamon et al (2020) indicated that tourist satisfaction significantly affects tourist intention to visit during tourism experience.…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…Besides, intention to visit was defined as individual's attitude response tendency to objects (Fishbein and Ajzen, 1977). The relationship between satisfaction and travel intention based on tourism experience has also been explored by previous studies (Cheunkamon et al, 2020;Neuts et al, 2013) According to previous literature review and hypotheses, the research model was illustrated in Figure 1.…”
Section: Authenticity Satisfaction and Intention To Visitmentioning
confidence: 99%
“…Num contexto tão competitivo como é o atual, de incerteza económica e com os problemas que se apontaram, que incidem na viabilidade económica dos estabelecimentos, o êxito dos destinos rurais vai depender, em grande medida, da lealdade turística, dado constituir uma promoção muito efetiva sem incorrer em importantes gastos de marketing (Neuts et al, 2013). Por lealdade entende-se a intenção de voltar a visitar e/ou recomendar o destino a outros (Halstead et al, 1994).…”
Section: Introductionunclassified